2020
DOI: 10.1007/s40328-020-00322-4
|View full text |Cite
|
Sign up to set email alerts
|

The application of inter-satellite links connectivity schemes in various satellite navigation systems for orbit and clock corrections determination: simulation study

Abstract: Inter-Satellite Links (ISLs) are intended to improve precision of orbit determination and satellite clock estimation. The ISLs provide a precise pseudorange measurements between satellites in a specific constellation. The study is a preparatory assessment of exploitation of seven connectivity schemes in the terms of the precise orbit determination for three types of constellations—Galileo-like with 24 satellites on three orbital planes, GPS-like with 24 satellites on six orbital planes, and GPS with real posit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…ISLs are considered crucial for enhancing the accuracy of orbit determination and satellite clock estimation [30]. This is improved using a combination of GS observations and ISLs, which eventually enhance the precision of navigation without supplementary GS network augmentation [31][32][33].…”
Section: Intersatellite Links For Spdopmentioning
confidence: 99%
“…ISLs are considered crucial for enhancing the accuracy of orbit determination and satellite clock estimation [30]. This is improved using a combination of GS observations and ISLs, which eventually enhance the precision of navigation without supplementary GS network augmentation [31][32][33].…”
Section: Intersatellite Links For Spdopmentioning
confidence: 99%
“…Bhardwaj et al [26] provided a brief review of satellite navigation, such as the working principle, position determination method, type of reference system for navigation applications, and satellite measurement technology. Kur et al [27] studied the intersatellite link (ISL) to improve the accuracy of orbit determination and satellite clock estimation. The preparatory evaluation for the development of seven connectivity schemes for the precise orbit determination of three types of constellations showed that the clock estimation errors of satellites and stations were almost equal for all the connectivity schemes used.…”
Section: State Of the Artmentioning
confidence: 99%
“…The accuracy of the time measurement is of the order of fraction of a nanosecond. The modern technologies like Inter-Satellite Links (Kur et al, 2020) or Cold Atom Interferometry (Travagnin, 2020) open the way to a further increase of the precision of positioning. Our results claim that the external Earth gravity field will be slightly twisted, provoking small perturbations of some orbits.…”
Section: Effects On the Earth Gravity Field Modelmentioning
confidence: 99%